Factors That Influence The Incidence Of Stunting In The Working Area Of Petang II Health Center, Badung Regency - Fina Aryani Putri, Kadek; Ni Made Kurniati (Sean Institute, 2024)
Stunting in childhood has a negative impact, namely inhibiting growth, cognitive and motor development, thereby creating a risk of metabolic disorders in adulthood. One of the factors guaranteeing family food security that researchers need to study is that Belok and Pelaga villages are agricultural areas that should produce abundant food. To date, no research has been conducted regarding the factors that influence stunting in the Petang II Community Health Center working area, Badung Regency. The factors looked for include history of LBW, immunization status, exclusive breastfeeding, history of infectious diseases, mother's education level and family food security. This research is a quantitative analytical research with a case control design. This study used a sample of 31 stunted toddlers as the case group, and 31 well-nourished toddlers as the control group with a ratio of 1:1. The results showed that the variables of maternal education level (p=0.001) and family food security (p=0.000) were significant in the incidence of stunting, while the variables of history of LBW (p=0.394), immunization status (p=0.078), exclusive breastfeeding (p= 0.088), history of infectious disease (p=0.158) was not significant in the incidence of stunting.